Irish chronicles as sources for the history of northern Britain, A.D. 660-800 - Evans, Nicholas (The Innes review, 2018)
This article studies the subject matter, details, and vocabulary of the Irish chronicle record relating to northern Britain from A.D. 660 to 800 in order to establish its sources. It rejects theories that the record from 660 to 740 preserves Applecross, Northern British or Pictish chronicles, arguing that an Iona Chronicle' accounts for nearly all items for northern Britain, and some, but not all, for Ireland. The Iona Chronicle' was a contemporary text whose style and interests gradually evolved over the period. After 740 the more limited evidence indicates that Iona and somewhere in southern Pictland probably provided written notices of events, but that the record's final form was produced in Ireland. The combination of common features and regional variation reflects the existence of more multiple centres of recording' which provided written notices of events to the centres of chronicling' at Iona and later Ireland, where the surviving chronicle text was produced.